Analysis of parallel operation of autonomous wind power plants with asynchronous generators - Golovko, V.; Kostochka, I. (Energy and Automation, 2025)
The article presents an analysis of modern studies dedicated to the parallel operation of autonomous wind energy systems with asynchronous generators. The advantages and limitations of using asynchronous machines in decentralized power systems are considered, particularly their simple design, reliability, and cost-effectiveness. Various approaches to organizing parallel operation are analyzed, including the features of ensuring and maintaining self-excitation, the use of capacitor banks, connection schemes for generators of different capacities, and methods of voltage and frequency regulation. Special attention is paid to the role of mathematical and simulation modeling, as well as experimental studies, which make it possible to evaluate the efficiency of systems under variable operating conditions. The prospects of applying controllers, especially those based on fuzzy logic, to enhance the stability and efficiency of autonomous power systems are also discussed. Based on the analysis, directions for further research are identified, particularly the need for a comprehensive consideration of transient processes, wind speed fluctuations, and the impact of load characteristics on the operation of parallel-connected generators.         Key words: renewable energy sources, wind energy, wind power plant, asynchronous generator, parallel work, autonomous work